2005
DOI: 10.1016/j.crhy.2004.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic anisotropy from single atoms to large monodomain islands of Co/Pt(111)

Abstract: By studying the magnetic behavior of self-assembled Co islands on a single-crystal metal surface, Pt(111), we show how the magnetic anisotropy evolves from isolated atoms to monolayer islands and films. Single Co adatoms are found to have a giant magnetocrystalline anisotropy energy of E a = 9.3 ± 1.6 meV/atom arising from the combination of partly preserved orbital moments (m L = 1.1 µ B ) and strong spin-orbit coupling induced by the Pt substrate. Combined scanning tunneling microscopy and X-ray magnetic cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 79 publications
(107 reference statements)
1
23
1
Order By: Relevance
“…Upon annealing Ostwald ripening sets in, yielding islands of well-controlled size and narrow size distribution. Thus, for Co in contact with Pt the variation of MAE from single atoms to bulk was fully spanned for the first time [32,33] (Figure 1c) [34]. These studies confirm that the magnitude of Es increases dramatically from surfaces, to steps, then to kinks or atoms.…”
Section: Surface Anisotropy In Nanostructuressupporting
confidence: 68%
“…Upon annealing Ostwald ripening sets in, yielding islands of well-controlled size and narrow size distribution. Thus, for Co in contact with Pt the variation of MAE from single atoms to bulk was fully spanned for the first time [32,33] (Figure 1c) [34]. These studies confirm that the magnitude of Es increases dramatically from surfaces, to steps, then to kinks or atoms.…”
Section: Surface Anisotropy In Nanostructuressupporting
confidence: 68%
“…A system which has been intensively investigated experimentally [3,4,5,6,7,8,9,10] as well as theoretically [11,12,13,14,15] in recent years is Co/Pt(111) (used here as a short notation for Co clusters or nanostructures, respectively, deposited on a Pt(111) substrate) as this is a prototype to study the requirements on new high-density magnetic storage materials. Earlier theoretical works studied only rather small Co clusters or Co chains on Pt(111) [11,12,13,14], whereas only recently first qualitative results and trends based on a parameterised tight-binding approach were published for deposited structures of up to 37 Co atoms [15].…”
Section: Introductionmentioning
confidence: 99%
“…Following early predictions of interface-induced PMA by Néel [1] and subsequent confirmations in NiFe/Cu, Co/Pd, Co/Pt, Co/Au and Fe/Ag [2][3][4][5][6], a host of layered systems with surface-induced PMA has been proposed and studied [6][7][8]. New phenomena were discovered in these systems, such as enhanced spin and orbital magnetic moments [8][9][10][11][12][13][14]. It was demonstrated that PMA is driven by the orbital moment anisotropy, which couples the symmetry axes of the system to the spin magnetic moment [13,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%